Association between heart diseases, social factors and physical frailty in community‐dwelling older populations: The septuagenarians, octogenarians, nonagenarians investigation with centenarians study. Issue 10 (3rd September 2020) - Klinpudtan, Nonglak; Kabayama, Mai; Gondo, Yasuyuki; Masui, Yukie; Akagi, Yuya; Srithumsuk, Werayuth; Kiyoshige, Eri; Godai, Kayo; Sugimoto, Ken; Akasaka, Hiroshi; Takami, Yoichi; Takeya, Yasushi; et al.
Abstract : Aim: Heart diseases and social factors are associated with physical frailty, but there are few studies of older people living in the community. Consequently, the aim of this study was to examine the association between heart diseases, social factors and physical frailty in community‐dwelling older populations including the oldest‐old people. Methods: The cross‐sectional study included 1882 participants of community‐dwelling older and oldest‐old people. The survey site assessed questionnaires on medical history, social factors, blood samples and physical examination. Physical frailty was based on slow gait speed or weak grip strength. Associations were analyzed using multiple logistic regression with adjustments for covariate factors. Results: Subjects with heart disease had a higher prevalence of physical frailty than those without heart disease. After adjusting the covariate factors, heart diseases were associated with a slow gait speed (odds ratio [OR] = 1.62; 95% confidence interval [CI]: 1.13–2.32, P = 0.009). Frequency of going outdoors and direct interaction with relatives or friends were associated with a slow gait speed (OR = 0.83, 95% CI 0.75–0.91, P ≤ 0.001 and OR = 0.87, 95% CI 0.81–0.94, P < 0.001), and associated with physical frailty (OR = 0.80, 95% CI 0.72–0.89, P ≤ 0.001 and OR = 0.88, 95% CI 0.82–0.95, P = 0.002). Living alone and frequency of direct interaction with relatives or friends were associated with physical frailty in subjects with heart disease. Conclusions: Our findings indicate that in community‐dwelling older people, heart diseases and social factors were associated with physical frailty. Older people with heart disease, those living alone and the frequency of direct interaction with relatives or friends were associated with physical frailty. Geriatr Gerontol Int 2020; 20: 974–979 .